Changing the Course of AIDS : Peer Education in South Africa and Its Lessons for the Global Crisis - Dickinson, David, 1963- (Book collections on Project MUSE., 2009)
Changing the Course of AIDS is an in-depth evaluation of a new and exciting way to create the kind of much-needed behavioral change that could affect the course of the global health crisis of HIV/AIDS. This case study from the South African HIV/AIDS epidemic demonstrates that regular workers serving as peer educators can be as--or even more--effective agents of behavioral change than experts who lecture about the facts and so-called appropriate health care behavior.After spending six years researching the response of large South African companies to the epidemic that is decimating their workforce as well as South African communities, David Dickinson describes the promise of this grassroots intervention--workers educating one another in the workplace and community--and the limitations of traditional top-down strategies. Dickinson's book takes us right into the South African workplace to show how effective and yet enormously complex peer education really is. We see what it means when workers directly tackle the kinds of sexual, gender, religious, ethnic, and broader social and political taboos that make behavior change so difficult, particularly when that behavior involves sex and sexuality.Dickinson's findings show that people who are not officially health care experts or even health care workers can be skilled and effective educators. In this book we see why peer education has so much to offer societies grappling with the HIV/AIDS epidemic and why those interested in changing behaviors to ameliorate other health problems like obesity, alcoholism, and substance abuse have so much to learn from the South African example.